2019
DOI: 10.18186/thermal.540043
|View full text |Cite
|
Sign up to set email alerts
|

CFD ANALYSIS OF LAMINAR FORCED CONVECTIVE HEAT TRANSFER FOR TiO2/WATER NANOFLUID IN A SEMI-CIRCULAR CROSS-SECTIONED MICRO-CHANNEL

Abstract: In this study, forced convection flow and heat transfer characteristics of TiO2/water nanofluid flow with different nanoparticle volume fractions (1.0%, 2.0%, 3.0% and 4.0%) in semi-circular cross-sectioned micro-channel was numerically investigated. The threedimensional study was conducted under steady state laminar flow condition where Reynolds number changing from 100 to 1000. CFD model has been generated by using ANSYS FLUENT 15.0 software based on finite volume method. The flow was under hydrodynamically … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(3 citation statements)
references
References 27 publications
0
3
0
Order By: Relevance
“…[31][32][33][34][35][36][37][38][39][40][41][42][43][44]. While CFD is an effective tool for numerical study, other numerical study involving ANN may be conducted for enhancing the results, as studies reported earlier have confirmed the same [45][46][47][48][49][50][51][52][53][54].…”
Section: Introductionmentioning
confidence: 92%
“…[31][32][33][34][35][36][37][38][39][40][41][42][43][44]. While CFD is an effective tool for numerical study, other numerical study involving ANN may be conducted for enhancing the results, as studies reported earlier have confirmed the same [45][46][47][48][49][50][51][52][53][54].…”
Section: Introductionmentioning
confidence: 92%
“…They conclude that the copper tube channels' thermal efficiency was significantly inserted with a twisted tap. Ekiciler [22] numerically investigated the heat transfer phenomenon of Al 2 O 3 nanoparticles with a volume fraction of 1% to 5% in a duct with a backwards-facing step. They observed that the Nusselt number and Reynolds numbers were directly proportional to the increase in the volume percentage of the Al 2 O 3 nanoparticles.…”
Section: Introductionmentioning
confidence: 99%
“…Another researcher Karimzadehkhouei et al [13] investigated the effect of inlet temperature for alumina-water nanofluid for thermally developing and hydrodynamically developed zone of laminar fluid flow whereas their results indicated that inlet temperature effects for thermally developing regions were more resulted and significant. Beside them, Singh et al [14], Iyahraja et al [15], Rabby et al [16], He et al [17], Kapıcıoğlu and Esen [18], Kaya et al [19], Ekiciler et al [20] also examined the impact of nanofluids on laminar convective heat transfer and their results also indicate the enhancement and improvement of heat transfer characteristics by the utilisation of nanofluids.…”
Section: Introductionmentioning
confidence: 99%